Effectiveness of personal protective health behaviour against COVID-19 - Chon Fu Lio; Hou Hon Cheong; Chin Ion Lei; Iek Long Lo; Lan Yao; Chong Lam; Iek Hou Leong (BMC, 2021)
Abstract Background Novel coronavirus disease 2019 (COVID-19) has become a pandemic, and over 80 million cases and over 1.8 million deaths were reported in 2020. This highly contagious virus is spread primarily via respiratory droplets from face-to-face contact and contaminated surfaces as well as potential aerosol spread. Over half of transmissions occur from presymptomatic and asymptomatic carriers. Although several vaccines are currently available for emergency use, there are uncertainties regarding the duration of protection and the efficacy of preventing asymptomatic spread. Thus, personal protective health behaviour and measures against COVID-19 are still widely recommended after immunization. This study aimed to clarify the efficacy of these measures, and the results may provide valuable guidance to policymakers to educate the general public about how to reduce the individual-level risk of COVID-19 infection. Methods This case-control study enrolled 24 laboratory-confirmed COVID-19 patients from Centro Hospitalar Conde de São Januário (C.H.C.S.J.), which was the only hospital designated to manage COVID-19 patients in Macao SAR, China, and 1113 control participants who completed a 14-day mandatory quarantine in 12 designated hotels due to returning from high-risk countries between 17 March and 15 April 2020. A questionnaire was developed to extract demographic information, contact history, and personal health behaviour. Results Participants primarily came from the United Kingdom (33.2%), followed by the United States (10.5%) and Portugal (10.2%). Independent factors for COVID-19 infection were having physical contact with confirmed/suspected COVID-19 patients (adjusted OR, 12.108 [95% CI, 3.380-43.376], P < 0.005), participating in high-risk gathering activities (adjusted OR, 1.129 [95% CI, 1.048-1.216], P < 0.005), handwashing after outdoor activity (adjusted OR, 0.021 [95% CI, 0.003-0.134], P < 0.005), handwashing before touching the mouth and nose area (adjusted OR, 0.303 [95% CI, 0.114-0.808], P < 0.05), and wearing a mask whenever outdoors (adjusted OR, 0.307 [95% CI, 0.109-0.867], P < 0.05). The daily count of handwashing remained similar between groups. Only 31.6% of participants had a sufficient 20-s handwashing duration. Conclusions Participating in high-risk gatherings, wearing a mask whenever outdoors, and practising hand hygiene at key times should be advocated to the public to mitigate COVID-19 infection.